Intrathermocline Eddies Embedded Within an Anticyclonic Vortex Ring. Issue 15 (1st August 2018) - Meunier, Thomas; Tenreiro, M.; Pallàs‐Sanz, Enric; Ochoa, Jose; Ruiz‐Angulo, Angel; Portela, Esther; Cusí, Simò; Damien, Pierre; Carton, Xavier
Abstract: High‐resolution hydrographic measurements reveal the presence of three intrathermocline eddies (ITEs) embedded within a loop current eddy. ITEs are lenticular bodies of nearly homogeneous water, which contrasts with the well‐stratified surrounding water. Their radii and thickness ranged between 19–32 km and 150–250 m. Negative relative vorticity within their cores (down to −0.85 times the Coriolis frequency), along with a large negative stratification anomaly, results in low Ertel potential vorticity and intense negative Ertel potential vorticity anomalies. Vortex stretching and relative vorticity have comparable contributions to potential vorticity anomaly, resulting in Burger numbers of order unity. The similarity of thermohaline properties within the ITE's cores and the surrounding loop current eddy water suggests that these ITEs likely form by intense mixing events followed by Rossby adjustment. Plain Language Summary: Small oceanic interior vortices, named intrathermocline eddies, were observed for the first time in the Gulf of Mexico using autonomous underwater gliders. These small eddies had the particularity to be embedded below a large and energetic anticyclonic eddy, which detached from the loop current 5 months before the survey. The physical properties of these structures are described, and their formation mechanisms, as well as potential impact on the redistribution of heat and salt in the Gulf of Mexico, are discussed. Key Points: Intrathermocline eddies were observed within the thermocline of a large anticyclonic loop current eddy They are characterized by weak stratification and low Ertel potential vorticity The observation of three ITEs in a single transect suggests that they could be abundant